Impact of Pesticide and Fertilizer on Human Health: A Case Study in Godawari Area, Lalitpur, Nepal (The Geographic Base, 2019)
Different types of pesticides and chemical fertilizers are in use in Nepal which is harmful for human health. These chemical fertilizers and pesticides are beyond the limitation and restriction. However, scientific study is very limited in Nepal. So, this study aims to assess the situation of use and protection system of pesticides users. This study is based on field level data of Godawari area of Lalitpur district. In Godawari area, Urea and DAP are mostly used for cereal crops and potash is mostly for vegetables. Pesticides and fertilizers are mostly used in vegetable farming but protection system during the use of pesticides and fertilizer is not satisfactory. So, these chemicals have been negatively affecting on the health of the local farmers.